Between the global and the private: the Second World War and the Cold War in two novels by Lithuanian-Canadians - Drewniak, Dagmara (My University, 2017)
This article offers an analysis of selected texts of Lithuanian-Canadian literature which concentrate on different perceptions of war. It explores the secret war of the 1940s led by the Lithuanian underground during the Second World War, as presented in Antanas Sileika’s Underground (2011), and the Cold War period analyzed by Irene Guilford in The Embrace (1999). Since these texts present certain marginalized, multicultural perspectives on conflicts and highlight the tensions in locations situated outside Canada, it is the ethnic perspective which allows the authors to introduce their stories into the Canadian literary scene. The article also raises questions concerning the links between family members torn apart by conflicts as well as dilemmas regarding heroism and betrayal. Finally, the influence of global conflicts on personal choices and identities is examined.
Keywords: Lithuanian-Canadian Literature; World War Two in Literature; Cold War in Literature; Antanas Sileika; contaminated landscapes; memory; Irene Guilford; diasporic literature